The Quality of Inpatient Health Services at Mamajang Health Center, Makassar City - Lusyana Aripa (Journal of Public Health and Pharmacy, 2021)
The quality of health services in the public or individual's need for health by standards with reasonable, efficient, effective use of resources within the limited capacity of the government and the community, and is carried out safely and satisfactorily by good norms and ethics. Based on the Health Center profile, the number of inpatients in 2017 was 51,155 people and increased in 2018 to 56,013. To find out how the quality of inpatient services at the Mamajang Health Center in 2020. This type of research is qualitative and uses a descriptive approach. The method of collecting data is using in-depth interviews (in-depth interviews). The number of informants in this study was five people by purposive sampling. The results of the study: 1) Tangible, the facilities and infrastructure of the Mamajang Public Health Center inpatient room were inadequate. 2) Reliability, inpatient health services at the Mamajang Health Center are accurate. 3) Responsiveness, health workers have not been effective in responding to patient complaints but are always ready and efficient to help patients. 4) Assurance, trusted health workers in providing information, but the cure of the disease depends on the accuracy of the drug. 5) Empathy from health workers who care for patients. It can be concluded that the quality of service at the Mamajang Health Center in Makassar City has not been maximized in providing services to inpatients.